Valgo dinâmico de joelho e sua relação com quadril, tornozelo e pé em atletas de futebol profissional - RIBEIRO, Diego Brenner (2018)
One of the most popular sports in the world is football, due to the characteristics imposed in the game, such as high explosive speed and physical contact, which demand strength, endurance and agility from its players. The high rate of injury in football can have serious consequences for athletes, the club and the whole system. In certain situations, these lesions are related to distal and proximal musculoskeletal structures of the lower limbs, such as forefoot alignment, isometric torque of hip abductors and passive medial hip rotation that influence medial rotation of the tibia and femur and forefoot pronation. This poor dynamic alignment of the lower limb in the frontal and transverse plane, especially dynamic valgus, may have relations with the ankle and foot joints. It is important that a good evaluation is performed in order to have important conclusions about the tests used and also to delineate the treatment. This study has already generated an article, already addressed to a specific journal and also other data that will be grouped in other articles. The article already submitted deals with reliability for evaluation. There are two reliability categories with respect to data collectors: reliability among multiple data collectors, which is inter-rater reliability, and reliability of a single data collector, which is called intra-rater reliability. The sample consisted of 29 professional soccer players (age 22.4 ± 4.3 years, body weight 73.7 ± 9.8 kg, height 179.0 ± 9.0 cm). All study participants were considered to be free of any musculoskeletal injury by club physiotherapists and were performing daily training tasks. Ankle dorsiflexion amplitude tests, forefoot alignment, passive hip rotation and kinematic knee evaluation were performed during the Step Down Test. From these data the intra and inter-rater reliability for the Step Down Test was performed. Two male evaluators participated in the study. For data of sample, mean and standard deviation were determined. For video analysis, the Kinovea®0.8.25 program was used. The intra and inter-rater reliability of all data was determined using the Pearson correlation coeficiente, with a confidence interval of 95% and p ≤ 0.05. The evaluator 1 was classified in the first step intra-rater of the analysis for heel touch with good to excellent reliability. For inter-rater analysis both for heel touch and for greater valgus angle, there was excellent reliability among the evaluators. There was no significant correlation between the hip, ankle and foot measurements in relation to the dynamic valgus bilaterally of the athletes. It was concluded that there is high inter-rater and intra-rater reliability through two-dimensional analysis using Step Down Test in professional soccer athletes. There is no relation of the passive hip, ankle and foot angular measures in relation to the dynamic knee valgus of soccer athletes, even when verifying in the study, values outside the normative standards established by other studies.